Reliability of the Alcohol use Disorders Identification Test (AUDIT) in Adolescents - Mattara, Fernanda Pavarina; Ângelo, Priscila Milene; Faria, João Bosco; Campos, Juliana Alvares Duarte Bonini (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2010)
The objective of this study was to estimate the reliability of the alcohol use disorders identification test (AUDIT) applied to adolescents. Evaluations were performed with 141 students of ages ranging from 14 to 17 years (14.93±0.62). The internal consistency of the instrument was estimated by Cronbach’s alpha coefficient and its reproducibility by weighted Kappa statistics by score and by a reliability interval of 95%. The AUDIT presented excellent internal consistency (α=0.80, rinter-item=0.29). Most questions present reproducibility ranked as “good”. It is concluded that the AUDIT is a reliable instrument to survey information about alcohol use in adolescents.